PENGARUH PENYULUHAN KELOMPOK DAN LEAFLET TERHADAP KEIKUTSERTAAN PEMERIKSAAN IVA - Nurhikmah; Budiman, Lisa (STIKES Pasapua Ambon, 2020)
Introduction :Based on Southeast Sulawesi data that existed in 2017 with the implementation of early detection through the inspection of Visual Acetic Acid Inspection (IVA) the highest Positive IVA is Muna Regency 11 cases or 26.19% in the first place is the Batukara health center with the next four (4) cases in the city of Kendari five (5) cases or 5.34%. Method : This type of research is an experimental study,the population in this study were all female couples in the fertile age, at Batukara Health Center, namely Moolo Village and Lanobake Village. The number of women of childbearing age in a row is 161 people and 90 people. The sample size is 54 respondents, the sampling technique uses proportional stratified random sampling. Data were collected using a questionnaire and then analyzed descriptively and inferentially using the Wilcoxon rank test formula and the mann-whitney test. Result : The results showed that group counseling and leaflets influenced knowledge, attitudes and participation in the examination of the Visual Acetate Acid Inspection (IVA) in the Batukara Health Center. Conclusion :It is necessary to hold health education about early detection of cervical cancer by utilizing counseling groups and leaflets to the community, especially young women so that they can carry out as early as possible routinely and regularly every schedule determined, so that it is expected to be able to detect cervical cancer early.